Politics and Religious Freedom in Indonesia: The Case of West Sumatra and North Sulawesi - SALIM, DELMUS PUNERI; SIMBUKA, SRIFANI; LUNTAJO, MUZWIR (Universitas Muhammadiyah Yogyakarta, 2016)
Since the introduction of decentralization, regions in Indonesia have promoted regional philosophies that guide their development. They apply said philosophies to many forms of development, including politics, economics, and administration. This paper examines the political discourse of religious freedom in West Sumatra and North Sulawesi, where the term ‘religious freedom’ has been variously interpreted to suit their regional philosophies.This paper includes examining religious freedom in regulations on religious interactions in Indonesia and shows that regulations below the Indonesian constitution have questioned religious freedom and played an important role in the political discourse of religious freedom in Indonesia and its provinces.This paper also examines how religious freedom in both West Sumatra and North Sulawesi is understood and explained by stakeholders. This picture is drawn from both Muslim and Christian religious leaders as well as governmental officials. The results show that West Sumatra’s Islamic philosophy have influenced the local understanding of religious freedom, whereas North Sulawesi’s philosophy of plural society has lead the term of religious freedom to be understood as religious pluralism. This paper questions relationship between national and regional governments over religion in Indonesia.